Human resources in industrial tourism - Pavlakovič, Barbara (Academica turistica, 2020)
Industrial tourism, as a specific type of tourism, emerged over a century ago but was not studied widely until recently. However, most of the current research is focused either on heritage industrial tourism or on several aspects, such as visitor characteristics, relation to the local economy, and similar. This paper attempts to highlight the human resources aspect of industrial tourism in different organisations.Our primary research methods were observation with participation (joining factory tours) and semi-structured interviews with company representatives.We define various existing categories of industrial tourism human resourcesmodels of organisations that carry out industrial tourism, the necessary competences for the workplace, and the methods of educating industrial tourism employees. Based on the gathered results, we propose some guidelines for companies to follow in forming their products of industrial tourism.
Keywords: competence; education; HR; HR model; industrial tourism; industrija; industrijska dediščina; kadri; kadrovska dejavnost; turizem